Juridical-Sociological study of land pawn : a normative study in Patilanggio district - Nasrullah Nasrullah (Jurnal Hukum Volkgeist, 2020)
The practice of land pawning in Patilanggio district still keeps the provisions of the applicable laws and regulations. So that it is more likely to harm the pledge grantor which is not based on the principle of helping. Although the community realizes that pawning land is harm for them, this is still done by residents as the last solution to meet urgent needs. This practice has become a habit and it is normal for community and never be a problem between the land pawner and the land pawn recipient. In disputing resolution between the grantor and the recipient, is by way of deliberation, involving the village head or only by deliberation between the pawner and the pawn recipient. Keywords: Pawner, recipient, Patilanggio